Determining Marketing Strategy At LPP TVRI Riau Using SWOT Analysis Method - Muhammad Rizki; Afdal Ghifari; Wang Ling Hui; Ekie Gilang Permata; Mhd. Dany Siregar; Muhammad Isnaini Hadiyul Umam; Harpito Harpito (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2021)
The purpose of this study was to use the SWOT approach to assess LPP TVRI Riau's marketing strategy. The focus of this research is to figure out internal and external factors in the SWOT analysis. This study used descriptive quantitative method. Sampling was performed by using probability sampling method with a total of 400 respondents from 6,394,087 populations from Riau Province. The questionnaire was designed by determining the level of importance and assessing the current conditions. Based on the results of the SWOT compilation, there are 5 strengths, 5 weaknesses, 4 opportunities, and 5 threats. Furthermore, weighting, rating, and scores are carried out at the IFAS and EFAS stages, for the weighting assessment carried out on the company side. The company's position is in quadrant II, which means that the company has more dominant strengths and threats, so that the company should support the diversification strategy policy. So that the SWOT matrix mapping can be done to produce four strategic policy alternatives, namely SO, ST, WO, WT.